(3GdMQhH GdLOjOI hGdJMhd aj eaGgje GdbhI HYO GdMQH GdHGQOI (B/s - (3GdeMeOGhj, bjS Ndas ((3YeGf (B[(3GdCQOf(B] :s (3OGQ CeLO ddfTQ hGdJhRjY WHGYI(B-(3fTQ(B-(3JhRjY ;s [(3ecGf GdfTQ ZjQ eMOO(B] :s (3EHUGQ fGTQhf hehRYhf (B:s (3OGQ caGAI GdeYQaI WHGYI(B-(3fTQ(B-(3JhRjY,s, 2023)
(3jJfGhd gPG GdcJGH hHQDjI TGedI XGgQI GdMQhH GdLOjOI GdJj QGabJ GdYbO GdChd hGdKGfj hGdKGdK ef GdCdajI GdKGdKI HGYJHGQgG XhGgQ fJLJ Yf GdeJZjQGJ GdYejbI hGdeDKQI aj JMhdGJ eaGgje GdbhI HYO GdMQH GdHGQOI hGdJj CaVJ dGMbG Edi XghQ CLjGd LOjOI ef GdMQhH ZjQ GdJbdjOjI HfeW hhSGFd hCSGdjH PGJ CgOGa eZGjQg Yf GdMQhH GdSGHbI, EP JJSe gPg GdMQhH HGdWGHY GdJcfhdhLj heNQLGJ GdKhQI GdeYdheGJjI GdJj CSgeJ HXghQ feW GdbhI GdSjHQGfjI PGJ GdbOQI Ydi CMOGK GdJCKjQ aj GdHfjI GdJMJjI GdeYdheGJjI hGdLZQGajI GdGaJQGVjI deYXe GdOhd hef NdGd YedjGJ (B((3GdbQUfI GdEdcJQhfjI, GdJLSS GdSjHQGf GdGNJQGb hGdGJdGa hGdJOejQ ddHjGfGJ(B) (3hebGHd Pdc GdbOQGJ GdSjHQGfjI aj GdUGdGJ GdCef hGdQOY GdTgjQGfj ddOhd haj ebOeJgG GdhdGjGJ GdeJMOI GdCeQjcjI hQhSjG hGdUjf OhdjG, hEjQGf (B((3hESQGFjd(B) (3EbdjejG, ceG jVY GdcJGH JhUjaG ObjbG dMQhH hSjGSGJ GdghjI hGSJQGJjLjGJ JaLjQ GdUQGYGJ ef GdOGNd PGJ GdGfJTGQ GdCabj ddJgOjOGJ hOhQ GdahGYd ef ZjQ GdOhd eSGMI Jdc GdJgOjOGJ GdJj JDKQ aj HjFI GdJaGYdGJ GdOhdjI hHPdc jYGdL GdcJGH HWQjbI CcGOjejI hJWHjbjI dXGgQI JCUjd GdYdGbI Hjf GdMQhH GdLOjOI hGdJMhd aj eaGgje GdbhI(B.s
(3HHdjhLQGajI (B: (3UaMI (B333-359.s
(3jTJed Ydi edNU HGddZI GdEfLdjRjI(B.s
Keywords: (3GdefGRYGJ GdOhdjIs; (3GdMQH GdHGQOIs; (3Gdbhi GdYXeis